2014
DOI: 10.5424/sjar/2014123-5365
|View full text |Cite
|
Sign up to set email alerts
|

Broadening the genetic base of Abyssinian mustard (Brassica carinata A. Braun) through introgression of genes from related allotetraploid species

Abstract: Brassica carinata (BBCC, 2n=34) has still to emerge as a major oilseed crop owing to poor agronomic attributes like long stature, long maturity duration and low seed yield. The restricted amount of genetic variability available in natural B. carinata necessitates utilization of new sources of variability for broadening its genetic base. Interspecific hybridization followed by selection in selfed and back cross progenies was employed to generate useful variability into B. carinata cv ˈPC5ˈ from elite lines of B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Our identification of Bc subgenome dominance in the B. carinata genome will significantly aid efforts in its improvement as a biofuel resource. Efforts for crop improvement, such as addressing the plant's tall stature and long life cycle, have been thwarted by the species' lack of genetic diversity (Sheikh et al, 2014). Our comprehensive characterization of the B. carinata could advance crop improvement efforts, including those of other Brassica spp.…”
Section: Unprecedented Retention Of Transposon Insertions In Gene Regionsmentioning
confidence: 99%
“…Our identification of Bc subgenome dominance in the B. carinata genome will significantly aid efforts in its improvement as a biofuel resource. Efforts for crop improvement, such as addressing the plant's tall stature and long life cycle, have been thwarted by the species' lack of genetic diversity (Sheikh et al, 2014). Our comprehensive characterization of the B. carinata could advance crop improvement efforts, including those of other Brassica spp.…”
Section: Unprecedented Retention Of Transposon Insertions In Gene Regionsmentioning
confidence: 99%
“…Moreover, B. carinata (BBCC) is endowed with many agronomically desirable traits such as resistance/tolerance to abiotic stresses (drought and heat); and biotic stresses, viz., aphid, Sclerotinia rot, white rust, Alternaria blight, blackleg, and powdery mildew [15]. Successful attempts of interspecific hybridization were made to transfer favourable alleles from B. carinata to B. rapa [16,17], B. napus [18], and B. juncea [7,14,[19][20][21]. Nikzad et al [22] used B. oleracea to exploit heterosis in hybrids between B. napus and B. oleracea; and suggested that the C genome of B. oleracea has potential to improve the seed yield in hybrid cultivars.…”
Section: Introductionmentioning
confidence: 99%
“…Although this species has tall plant stature, poor seed characteristics, and takes longer to mature (Supplementary Table 1), when compared to B. juncea, it possesses many agronomically desirable traits including resistance or tolerance to most of the abiotic and biotic stresses like drought, heat, aphid, Sclerotinia rot, white rust, Alternaria black spot, blackleg, and powdery mildew (Raman et al, 2017;Thakur et al, 2019), which are otherwise eliminated from the predominantly cultivated Brassica species during domestication. Therefore, efforts toward interspecific hybridisation were made in the past to transfer desirable traits from B. carinata to cultivated Brassica species viz., B. rapa (Jiang et al, 2007;Choudhary et al, 2008), B. napus (Navabi et al, 2011;Sheikh et al, 2014), and B. juncea (Getinet et al, 1994;Sheikh et al, 2014;Singh K. H. et al, 2015). B. carinata is known to be the most drought tolerant among cultivated Brassica species as it develops sufficient biomass and seed yield even under the water deficit stress conditions.…”
Section: Introductionmentioning
confidence: 99%